LITERATURE REVIEW: METHODS FOR TREATING SCHOOL REFUSAL IN CHILDREN AND TEENAGER - Hasanah, Intan Hafizha; Hasan, Fadilla Rifky; Sari, Indah Cyntia; Nurani, Gita Aulia (Journal of Psychology Students, 2022)
School is a formal education that is used as a form of developing character values and norms that apply in society. The existence of a school does not rule out the possibility that students also have problems they have, one of which is school refusal. The causes of school refusal include avoiding school-related objects that cause stress, avoiding feelings of discomfort among peers, seeking attention outside of school, and pursuing pleasure outside of school. This study aims to determine the ef ective method in handling school refusal in children and adolescents. This study uses a literature review method with techniques for collecting information and data from various materials in libraries and other sources as a method of research. As many as 14 journals are used as a reference with the literature review method, it can be concluded that the results of this study indicate that there are factors from school refusal including anxiety, forms of protective parenting, dif iculties in following lessons at school, bad experience in school past. Therefore, based on the research results several methods that can be used to reduce school refusal include CBT counseling, REBT counseling, family-based therapy, cognitive restructuring techniques.